Ответ:
Пошаговое объяснение:
3 * (х-2)/5 - 2(1+х)/4 = (х-4)/3 | *60
12 * 3(х-2) - 15*2(1+х) = 20(х-4)
36(х - 2) - 30(1 + х) = 20(х - 4)
36х - 72 - 30 - 30х = 20х - 80
6х - 102 = 20х - 80
6х - 20х = -80 + 102
-14х = 22
х = 22 : (-14)
х = -22/14
х = -11/7
х = -1. 4/7
7х + 10 = 7*(-1. 4/7) + 10 = 7*(-11/7) + 10 =
-77/7 + 10 = -11 + 10 = -1
Ответ: -1
Ответ
на фото
Обьяснение;
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
3 * (х-2)/5 - 2(1+х)/4 = (х-4)/3 | *60
12 * 3(х-2) - 15*2(1+х) = 20(х-4)
36(х - 2) - 30(1 + х) = 20(х - 4)
36х - 72 - 30 - 30х = 20х - 80
6х - 102 = 20х - 80
6х - 20х = -80 + 102
-14х = 22
х = 22 : (-14)
х = -22/14
х = -11/7
х = -1. 4/7
7х + 10 = 7*(-1. 4/7) + 10 = 7*(-11/7) + 10 =
-77/7 + 10 = -11 + 10 = -1
Ответ: -1
Ответ
на фото
Обьяснение;